RISK AND PROFIT ANALYSIS IN INVESTMENT DECISIONS ON AGGRESSIVE INVESTORS IN JAVA ISLAND IN 2020 AN EMPIRICAL STUDY ON THE INDONESIAN CAPITAL MARKET - Wahbi, Abdul Azim; Syahrudi, Syahrudi; Sahrudin, Sahrudin (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Objective: This study examines the relationship between investment decisions, high-risk profiles, and medium-risk profiles with emotional anxiety among aggressive investors in Java during 2020, addressing the underexplored psychological dimensions of investor behavior. Method: Adopting a quantitative observational research design, the study utilized panel data comprising 20 observations from 7 cross-sections over the 2020–2022 period. Panel regression analysis was conducted to assess the impact of the variables on emotional anxiety, with data sourced from credible institutions to ensure reliability. Results: The findings indicate that investment decisions, high-risk profiles, and medium-risk profiles do not significantly influence the emotional anxiety of aggressive investors. A low R-squared value suggests that these variables account for only a small proportion of the observed variation in emotional anxiety. Novelty: This study provides fresh insights by highlighting the limited explanatory power of traditional financial and risk-related factors on emotional anxiety, suggesting the need to explore broader psychological and behavioral elements. These findings emphasize the importance of integrating emotional factors into risk management strategies, enabling policymakers and practitioners to better address investor resilience amidst market volatility. By focusing on the intersection of financial and psychological aspects, this research contributes to a nuanced understanding of aggressive investor behavior in the Indonesian capital market.